PENGARUH SIKAP TENAGA KESEHATAN DAN KETERSEDIAAN OBAT TERHADAP TINGKAT KEPUASAN MASYARAKAT PEMEGANG KARTU JAMKESMAS RUMAH SAKIT AHMAD RIPIN KABUPATEN MUARO JAMBI - Rohima, Ananda Putri (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
This study aims to find out the influence of the attitude of health workers and the availability of drugs on the level of community satisfaction of jamkesmas cardholders of Ahmad Ripin Hospital Muaro Jambi Regency, both independently and simultaneously. This research uses a quantitative approach. The type of research used is ex-post facto. The variables used in the study were the attitude of health workers, the availability of drugs and the level of satisfaction. The data collection techniques used in the study used questionnaires, observations, documentation and interviews. Sampling technique uses probability sampling with a sample number of 250 patients. The subjects of the trial were as many as 30 patients at Abdul Manap Hospital in Jambi City. Instrument trials are conducted to determine the validity and reliability of the instrument. The validity of the instrument is calculated using the Product Moment Correlation Analysis and obtained 47 valid items. Test the reliability of the instrument using The Cronbach Alpha and all variables have high reliability. The data analysis techniques used are simple regression analysis techniques and double regression analysis. The results of this study showed that (1) there was a positive and significant influence of the attitude of health workers towards the level of community satisfaction of jamkesmas cardholders of Ahmad Ripin Hospital Muaro Jambi Regency which was shown by rhitung > rtabel 5% of 0.409 > 0.138, (2) the influence there was a positive and significant increase of the availability of drugs to the level of satisfaction of the community of jamkesmas card holders of Ahmad Ripin Hospital Muaro Jambi Regency indicated by rhitung > rtabel 5% of 0.355 > 0.138, and (3) there was a positive and significant influence of the attitude of health workers and the availability of drugs to the level of community satisfaction of jamkesmas card holders of Ahmad Ripin Hospital Muaro Jambi Regency indicated by Fhitung > Ftabel 5% of 35,111 > 3.04. The study's effective contribution was 22.1%, while 77.9% was explained by other factors not analyzed in the study.